2015
DOI: 10.18632/oncotarget.4541
|View full text |Cite
|
Sign up to set email alerts
|

A long noncoding RNA AB073614 promotes tumorigenesis and predicts poor prognosis in ovarian cancer

Abstract: Long noncoding RNA (lncRNA) profiles in ovarian cancer (OC) remain largely unknown. In the present study, we screened AB073614 as a new candidate lncRNA which promotes development of OC, in two independent datasets (GSE18521 and GSE38666) from the Gene Expression Omnibus (GEO). The level of AB073614 was then detected in 75 paired OC tissues and adjacent normal tissues by qRT-PCR. Results showed that AB073614 expression was significantly up-regulated in 85.3% (64/75) cancerous tissues compared with normal count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 24 publications
1
67
0
Order By: Relevance
“…However, the level of lncRNAs expression is associated with disease prognosis, patients' survival, and therapeutic response [14,15] . In addition, their expression has been found to be significantly regulated by estrogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the level of lncRNAs expression is associated with disease prognosis, patients' survival, and therapeutic response [14,15] . In addition, their expression has been found to be significantly regulated by estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be up-regulated in 85.3% of ovarian cancerous tissues compared with normal counterparts [15] . Besides, patients with high expression of AB073614 had a lower 5-year overall survival in comparison with low expression group.…”
Section: Ab073614mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, poor prognosis (shorter OS) is associated with high expression of nuclear paraspeckle assembly transcript 1 (NEAT1) [79], ANRIL [63], and AB0736614 in patients with OC [69]. Furthermore, both shorter OS and disease-free survival (DFS) were associated with up-regulated CCAT2 [62] and HOXA11as [66], whereas low expression of GAS5 was associated with shorter OS and DFS in patients with OC [61].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…7 Among them, lncRNAs have acquired extensive attention, recently, as new regulators in many biological processes, such as transcriptional regulation, 8 differentiation, 9 immune response, 10 metabolism, 11 cell growth, and especially tumorigenesis. 12,13 Moreover, since an increasing number of reports have indicated that their abnormal expression is frequently observed in human cancers, some lncRNAs have been validated as biomarkers for diagnostic, metastasis, recurrence, and poor prognosis, [14][15][16][17] such as MALAT-1 for lung, glioma, gastric, and prostate cancer; [18][19][20][21] HOTAIR for breast, ovarian, pancreatic, and colorectal cancer; [22][23][24][25] and CCAT2 for oral squamous cell carcinoma and bladder cancer. 26,27 Zinc finger antisense 1 (ZFAS1) locus is host to three C/D-box small nucleolar RNAs (snoRNAs), and its transcription initiates from the antisense strand near the 5â€Č end of the protein-coding gene Znfx1.…”
Section: Introductionmentioning
confidence: 99%